العلاقة بين اقتصاد الظل والمؤشرات الاقتصادية الكلية في سورية - محمود, يوسف; موسى, رلا (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يعتبر اقتصاد الظل من أهم المشكلات الاقتصادية التي مازالت تأخذ الحيز الواسع من اهتمامات الباحثين ، وذلك لارتباطه بكافة المتغيرات الاقتصادية، فهو موجود في جميع الدول على اختلاف أنماطها الاقتصادية ولكنه أوسعُ انتشاراً في الاقتصاديات النامية ويتضمن في طياته أنشطة مشروعة وأخرى غير مشروعة. و هو موجود في كافة المستويات الاقتصادية ويمس كافة الشرائح الاجتماعية ويضم كافة المراحل العمرية ، وبالرغم من توصيفه كظاهرة لا يمكن التغاضي عن كونه واقعاً قائماً ومستمراً . بناء على ماتقدم جاء هذا البحث لتوضيح مفهوم اقتصاد الظل ، والتعرف على مكوناته كذلك يوضح البحث أهم حسابات الدخل القومي ودرجة ارتباطها باقتصاد الظل وبيان أثر بعض المتغيرات الاقتصادية على اقتصاد الظل. Shadow economy is considered the most important economic problem which is still of concern to researchers for it is linked to all economic variables. It is found in all States with different economic patterns. But it is more widespread in developing economies includes a recipe for lawful activities and other illegal .And it exists in all economic levels and affect all social strata and in all ages. Despite its characterization as a phenomenon, it cannot be overlooked as a reality. Depending on that, this research tried to clarify the concept of the shadow economy, and identify its components. As well as, this research shows the most important macroeconomic indicators in Syria and the impact of economic variables on the shadow economy.